Assessment of microleakage of class V restored by resin composite and resin-modified glass ionomer and pit and fissure resin-based sealants following Er:YAG laser conditioning and acid etching: in vitro study - Luong E; Shayegan A (Dove Medical Press, 2018)
Emilie Luong,1 Amir Shayegan2 1Department of Children and Adult Operative Dentistry, César de Paepe Hospital, Free University of Brussels, Bruxelles, Belgium; 2Department of Children and Adult Operative Dentistry, Children’s Hospital of Queen Fabiola, Free University of Brussels, Bruxelles, Belgium Aim: The aim of this study was to make a comparison between microleakage of conventionally restored class V cavities using acid etchant and the ones conditioned by erbium-doped yttrium aluminum garnet (Er:YAG) laser, and also to assess and compare the effectiveness of enamel surface treatments of occlusal pits and fissures by acid etching and conditioned by Er:YAG laser-etch.Materials and methods: Seventy-two extracted third molars were used in this study. The samples were divided into two major groups: class V cavities and pit and fissure sealants. Each subgroup was divided into conventional acid etching, Er:YAG laser conditioning and conventional acid etching, and combination with Er:YAG laser conditioning (n=12). The teeth were placed in 2% methylene blue dye solution, were sectioned, and were evaluated according to the dye penetration criteria. Two samples per subgroup were chosen for scanning electron microscopic (SEM) analysis.Results: There was a significant difference between occlusal and cervical margin groups. Laser conventional composite cementum group showed more microleakage values compared to other groups. There was no significant difference between occlusal margin groups. However, there was a significant difference between cervical margin groups in terms of microleakage. In sealant groups, there was a significant difference between laser and conventional with/without laser treatment groups in terms of microleakage.Conclusion: Based on the results reported in this study, it can be concluded that the application of the Er:YAG laser beneath the resin composite, the resin-modified glass ionomers (GIs), and the fissure sealant placement may be an alternative enamel and dentin etching method to acid etching. Keywords: Er:YAG laser, microleakage, etching